On the nature and physical conditions of the luminous Ly α emitter CR7 and its rest-frame UV components. Issue 2 (24th October 2018) - Sobral, David; Matthee, Jorryt; Brammer, Gabriel; Ferrara, Andrea; Alegre, Lara; Röttgering, Huub; Schaerer, Daniel; Mobasher, Bahram; Darvish, Behnam
ABSTRACT: We present new Hubble Space Telescope ( HST )/WFC3 observations and re-analyse VLT data to unveil the continuum, variability, and rest-frame ultraviolet (UV) lines of the multiple UV clumps of the most luminous$\rm {Ly \, α}$ emitter at z = 6.6, CR7 (COSMOS Redshift 7). Our re-reduced, flux-calibrated X-SHOOTER spectra of CR7 reveal an He ii emission line in observations obtained along the major axis of$\rm {Ly \, α}$ emission with the best seeing conditions. He ii is spatially offset by${≈ }\!+\!0.8\, $ arcsec from the peak of$\rm {Ly \, α}$ emission, and it is found towards clump B. Our WFC3 grism spectra detects the UV continuum of CR7's clump A, yielding a power law with$β =-2.5^{+0.6}_{-0.7}$ and$M_{\text{UV}}=-21.87^{+0.25}_{-0.20}$ . No significant variability is found for any of the UV clumps on their own, but there is tentative (≈2.2 σ) brightening of CR7 in F110W as a whole from 2012 to 2017. HST grism data fail to robustly detect rest-frame UV lines in any of the clumps, implying fluxes$\lesssim 2× 10^{-17}$ erg s −1 cm −2 (3σ). We performcloudy modelling to constrain the metallicity and the ionizing nature of CR7. CR7 seems to be actively forming stars without any clear active galactic nucleus activity in clump A, consistent with a metallicity of ∼0.05–0.2 Z⊙ . Component C or an interclump component between B and C may host a high ionization source. Our results highlight the need for spatially resolved information to study the formation and assembly of early galaxies.